2008
DOI: 10.2741/2937
|View full text |Cite
|
Sign up to set email alerts
|

Microglial degeneration in the aging brain - bad news for neurons?

Abstract: We have long promulgated the idea that microglial cells serve an entirely beneficial role in the central nervous system (CNS), not only as immunological sentinels to fend off potentially dangerous infections, but also as constitutively neuroprotective glia that help sustain neuronal function in the normal and especially in the injured CNS when microglia become activated. In recent years, we have reported on the presence of degenerating microglial cells, which are prominent in the brains of aged humans and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 207 publications
1
105
0
2
Order By: Relevance
“…It has been suggested that age-related neurodegeneration might not only be due to a loss of neuroprotective properties, but also the actual loss of microglia [40]. A recent hypothesis put forth to explain the phenotypic changes in aging microglia suggest that microglial senescence is triggered by an intracellular oxidative stress response due to enhanced intracellular accumulation of iron [41]. Under this hypothesis, an oxidative stress response, often attributed to microglia based primarily upon in vitro studies, would lead to senescence rather than activation.…”
Section: Development and Aging Of Microgliamentioning
confidence: 99%
“…It has been suggested that age-related neurodegeneration might not only be due to a loss of neuroprotective properties, but also the actual loss of microglia [40]. A recent hypothesis put forth to explain the phenotypic changes in aging microglia suggest that microglial senescence is triggered by an intracellular oxidative stress response due to enhanced intracellular accumulation of iron [41]. Under this hypothesis, an oxidative stress response, often attributed to microglia based primarily upon in vitro studies, would lead to senescence rather than activation.…”
Section: Development and Aging Of Microgliamentioning
confidence: 99%
“…With aging, iron dysregulation occurs (Daugherty et al, 2015), resulting in a chain of events that, although not fully elucidated, appear to be largely deleterious: for example, insidious damage to the blood-brain barrier (Farrall and Wardlaw, 2009) and excessive free radical generation inducing oxidative stress (Poon et al, 2004) are mechanisms thought to be associated with age-and disease-related iron accumulation. In addition, it is also thought that microglial activation stimulates iron uptake from damaged cells and downregulates export to exacerbate iron imbalance (Rathore et al, 2012), thus compromising microglial neuroprotection (Streit et al, 2008) and increasing neurotoxicity (Block et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the role of prostaglandins and underlying cell signaling after activation of lipopolysaccharide led to novel insights. [62][63][64][65][66] Since AD and PD are age-related disorders and microglia may change their functional properties in the aging brain, 67 protocols are in demand for the isolation of microglia from adult rodents. A few protocols exist; however, presently, literature is scarce on this topic.…”
Section: Microglia and Astrocytes In Ad And Pdmentioning
confidence: 99%